2002
DOI: 10.1560/rrxu-ex5y-qrxk-h1ha
|View full text |Cite
|
Sign up to set email alerts
|

Lichen flora of the Murgul district, Artvin, Turkey

Abstract: This study was carried out in the province of Artvin, district of Murgul. A total of 94 species in 41 genera belonging to Ascomycetes were found, two of which are varieties and three are subspecies. Eight of these species are new records for Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The samples were identified using various flora books and papers (Aslan, 2000;Aslan et al, 2002). The identified sample was air-dried and stored in the herbarium of Kaz|m Karabekir Education Faculty.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were identified using various flora books and papers (Aslan, 2000;Aslan et al, 2002). The identified sample was air-dried and stored in the herbarium of Kaz|m Karabekir Education Faculty.…”
Section: Methodsmentioning
confidence: 99%
“…and P. furfuracea (L.) Zopf were collected from the Giresun, Erzurum and Artvin province in Turkey, during summer of 2011. The samples were identified using various flora books and papers [12,21] . Identified samples were air-dried and stored in the herbarium of Kazım Karabekir Education Faculty, Atatürk University.…”
Section: Lichen Extractsmentioning
confidence: 99%
“…Lichen species are very common in Turkey. Unique lichen flora has attracted many researchers on the systematical basis [12] . It is pointed that lichens may be easily accessible sources of natural drugs that could be used as a possible food supplement or in pharmaceutical industry [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The lichen Cetraria Islandica (L.) Ach., used in this study was identified in the laboratory of lichenology at Department of Biology, Kazım Karabekir Education Faculty of Ataturk University by Dr. Aslan using various floras. [9][10][11][12][13][14][18][19][20][21] All samples were washed in distilled water and then dried at 70 -80 °C for 48 hours. [9][10][11][12][13][14] The dried lichens were ground in porcelain mortar and sieved into the following sizes: 75-180, 180-300, 300-425, 425-600 µm.…”
Section: Collection and Preparation Of Biomass Samplesmentioning
confidence: 99%
“…If lichen flora of Turkey is completely determined; reliable results will be obtained about air and heavy metal pollutions according to species amounts, species diversity in different areas and pollutant values in this species. [9][10][11][12][13][14][15] The major advantages of biosorption over conventional treatment methods include: low cost, high efficiency, minimization of chemical and biological sludge, no additional nutrient requirement, and regeneration of biosorbent and possibility of metal recovery. 2 The complex structure of micro organisms implies that there are many ways for the metal to be taken up by the microbial cell.…”
Section: Introductionmentioning
confidence: 99%